1998
DOI: 10.1542/peds.102.3.e35
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Physiologic Instability Is Associated With Neurodevelopmental Morbidity at One and Two Years in Extremely Premature Infants

Abstract: ABSTRACT. Objective. The objective of this study was to evaluate the relationships between chronic physiologic instability, as assessed by the cumulative daily Score for Neonatal Acute Physiology (SNAP), and neurodevelopmental morbidity in premature infants at 1 year and at 2 to 3 years of age.Design. The subjects of this retrospective study were extremely premature (<30 weeks' gestational age [GA]) infants born in 1993 and 1994 who were seen in follow-up at least once between 1 and 3 years of age. Cumulative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 35 publications
3
31
0
1
Order By: Relevance
“…Mattia et al 19,20 reported an association between cumulative illness severity and neurodevelopmental outcome in premature infants p30 weeks gestation at birth. Those in the highest quartile for cumulative SNAP score from their entire newborn hospitalization were more likely to have abnormal gross motor and psychomotor development at 2 to 3 years and 4 to 5 years of age than infants with a less severe hospital course.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mattia et al 19,20 reported an association between cumulative illness severity and neurodevelopmental outcome in premature infants p30 weeks gestation at birth. Those in the highest quartile for cumulative SNAP score from their entire newborn hospitalization were more likely to have abnormal gross motor and psychomotor development at 2 to 3 years and 4 to 5 years of age than infants with a less severe hospital course.…”
Section: Discussionmentioning
confidence: 99%
“…16 Cumulative SNAP score for the first 28 days of life (SNAP28) was calculated by addition of daily SNAP scores for each subject, using a modification of the method described by Mattia and deRegnier. 19 Thus, an infant with sequential daily scores of 20, 5, 17, 5 and 23 would have a 5-day cumulative score of 70. As described previously, 19 SNAP points for individual parameters were interpolated for up to 3 days where physiologically appropriate, if new values were not recorded.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…High CRIB and SNAPPE-II scores, which indicate increased medical risk and severity factors, are also predictors for neurobehavioral delays. 37,38 It is thus most important to note that these potential confounders were well matched between the three study groups. No differences in gestational age and birth weight between the three iron groups existed.…”
Section: Discussionmentioning
confidence: 99%